ANALISIS VARIASI TIPE EVAPORATOR DENGAN REFRIGERAN LPG TERHADAP UNJUK KERJA MESIN REFRIGERATOR - Alif Puspita Ningrum; Digdo Listyadi R. (ROTOR, 2016)
Refrigeration system is a system working for cooling temperature some goods or room with absorbs the heat. Refrigeration process is very important for store a food and beverage so will be able to keeep up in certain time, refrigerator development has achieve characteristic improvement about non-ODP (Ozone Depleting Potential) and non-GWP (Global Warming Potential) refrigerant as well as alternative refrigerant until now. The purpose of this research is to know about effect from variation evaporator type using LPG refrigerant againts refrigerator performance. Experimental methode did for the direct test to analyzed how much effect from variation evaporator type that are used in (serries one space, ser series two space, parallel one space, and parallel two space) useing C plate evaporator and compressor ¾ pk . This research are do it by installing an evaporator in each unit of refrigerator chamber top part and refrigerator chamber bottom part that arranged by series and parallel which is in each chamber have a breaker or without breaker. The result from the research variation  of evaporator  type for refrigerator is to know how much  the effect of  refrigeration,  compression  working, refrigeration capacity, and Coefficient Of Performance (COP). The lowest temperature is shown from evaporator type series one space, that have a value -21,2 OC. The lowest interval from both of chamber type is shown from evaporator type parallel two space, that have a value 3,64 OC. Coefficient Of Performance (COP) from series type is 9,06 for one space and 9,01 for two space, then from parallel type is 10,59 for one space and 13,43 for two space. Based from research the acquired result that is from using evaporator series type and parallel type is could be used for cooling down several room in refrigerator.